2000년대 한국의 ‘탈민족주의’ 논쟁 연구: 주요 쟁점과 기여 - 전재호; Jaeho Jeon (한국과 국제정치, 2018)
이 글은 2000년대 한국 학계를 뜨겁게 달군 탈민족주의 논쟁을 다루었다. 탈민족주의론은 포스트모더니즘의 시각에서 민족주의의 부정과 해체를 지향하는 담론으로 기존의 민족주의 인식을 비판했고, 기성 학계는 이러한 비판에 대해 재비판, 수용, 변용 등 다양한 대응을 보였다. 탈민족주의 논쟁은 1990년대 지구화의 급속한 확산, 이주민의 대량 유입, 한중일 민족주의의 충돌이라는 현실을 배경으로, 서구의 근대론적 민족주의 인식과 포스트모더니즘이라는 이론들로부터 영향을 받았다. 이 글은 논쟁의 주요 쟁점들 중 탈민족주의의 인식론적 전제인 한민족 형성의 근대론, 이론적 기초인 포스트모더니즘과 포스트모던 역사인식, 이데올로기 차원에서 권력 담론으로서의 민족주의, 그리고 현실적 차원에서 민족주의에 대한 비판인 탈민족·탈국가 역사 인식/서술과 국사해체론을 다루었다. 이 쟁점들을 중심으로 탈민족주의론의 기존 입장에 대한 비판과, 그에 대한 기성 학계의 대응을 정리했다. 2000년대 후반 탈민족주의 논쟁은 논쟁을 주도했던 역사포럼의 해체, 한국을 둘러싼 역사적이고 현실적인 조건의 변화, 탈민족주의론의 한계 등을 배경으로 잠잠해졌다. 그럼에도 불구하고 논쟁은 그동안 비판의 성역이던 한국민족주의에 대한 성찰을 가져왔고, 그 결과 민족주의의 역할과 효용성을 재검토하도록 했으며, 민족주의의 변용과 대안 모색을 추구하도록 했다는 점에서 학술적 의의를 갖고 있다. This article examines the debate around nationalism and post-nationalism that occurred within the Korean academia in the 2000s. Post-nationalism is a postmodernism-based discourse that both deconstructs and negates theories of nationalism. When scholars criticized the existing nationalist discourse from the perspective of post-nationalism, the existing scholarship of nationalist theories responded variously with either counter-criticisms, acceptance of contrasting theories, and adaptations of their theories. The backdrop of this debate was several different changes in Korean society in the 1990s, including the rapid expansion of globalization, mass labor migration into Korea, and increasing nationalist conflicts among Korea, China, and Japan. Academically, this debate was also influenced by the introduction of modernism-based understanding of nationalism and postmodernism into Korean academia. The main arguments in this debate concern: the theory that the Korean nation was formed during the modern period, the theory of postmodernism and a postmodernist understanding of history, the postmodernist understanding of nationalism as an ideology and discourse of power, and the argument in favor of post-national and post-state perceptions and descriptions of Korean history and the deconstruction of nationalist history. My examination focuses on the debate between the post-nationalist criticism of existing nationalist approaches and the responses to this criticism by existing scholarship. Toward the late 2000s, this debate died down as a result of several factors: the dissolution of the “History Forum” which had led this debate, the changes in the political, economic, and social climate in and around Korea, and the internal conceptual and practical limitations of post-nationalism theory itself. Nonetheless, this debate made a valuable contribution to Korean scholarship by leading it to reflect on nationalism which had been a sacred taboo and beyond criticism in Korea, to re-examine the role and function of nationalism, and to explore the possibility of transforming and/or creating alternatives to nationalism.